PEMANFAATAN TEKNOLOGI MULTIMEDIA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Suhirman, Suhirman (Madania: Jurnal Kajian Keislaman, 2015)
Using Multi-media Technology in Teaching-learning Interaction of Islamic Education. This article isaimed at discussing about multi-media technology benefit in learning process for Islamic education. Multi-mediatechnology makes learning more effective in accomplishing knowledge, skills, attitudes as well as encouragesthinking, feeling, attention, and students’ motivation in order to make learning process become moremeaningful, having purpose, and more comfortable. It also expects that such multi-media technology is used toexplore the meaning of Islamic education from various dimensions that can be implemented in academic fieldby applying those technologies in the context of teaching-learning interaction